Gender differences in tibial acceleration in pre-season youth soccer players - Carlson, T.; Melaro, J.; Weinhandl, J. T. (ISBS Proceedings Archive (Michigan), 2023)
In soccer, the players need to be able to change direction quickly, meaning the players need the ability to rapidly accelerate and decelerate. Females at a young age have a higher risk of sustaining injuries that can be caused by rapidly accelerating compared to males. The purpose was to investigate the gender differences in acceleration in youth soccer players. 30 youth soccer players engaged in the following drills: a jog, the M drill, 5-10-5 drill, and a single leg triple jump. This data was collected using inertial measurement units. The peak accelerations in the M drill on the left side was the only statistically significant drill (p=0.006, females: 590.9 ± 275.9 m/s2, males: 882.1 ± 263.4 m/s2). There is support to add load management strategies to current training programs and that individualized programs may be the most effective.